Enzymatic release of 7-methylguanine from methylated DNA by rodent liver extracts. - Margison, G P (1981)
Rat and hamster liver extracts were found to contain DNA glycosylases capable of removing 3-methyladenine and 7-methylguanine from methylated DNA. The activity of 7-methylguanine-DNA glycosylase was greater tin hamster than in rat liver extracts. This finding is consistent with previous reports that the half-life of 7-methylguanine in DNA after treatment with the carcinogen dimethylnitrosamine is longer in rats than in hamsters. These enzymes may, therefore, play an important role in the removal of abnormal alkylation products from mammalian cell DNA. Rodent liver extracts also contained a DNA glycosylase able to remove from alkylated DNA the imidazole-ring-opened form of 7-methylguanine which is produced by treatment with alkali. Although this product may occur in vivo after treatment with alkylating agents to only a very small extent, the enzyme may be needed to minimize its potentially harmful biological effects.